Film Serials and the American Cinema, 1910-1940 Operational Detection - Brasch, Ilka; Project Muse. (2018)
Before the advent of television, cinema offered serialised films as a source of weekly entertainment. This book traces the history from the days of silent screen heroines to the sound era's daring adventure serials, unearthing a thriving film culture beyond the self-contained feature. Through extensive archival research, Ilka Brasch details the aesthetic appeals of film serials within their context of marketing and exhibition and that they adapt the pleasures of a flourishing crime fiction culture to both serialised visual culture and the affordances of the media-modernity of the early 20th century. The study furthermore traces how film serials brought the broadcast model of radio and television to the big screen and thereby introduced models of serial storytelling that informed popular culture even beyond the serial's demise.
Cover; Table of Contents; Acknowledgements; 1. Introduction; 2. The Operational Aesthetic; 3. Film Serials Between 1910 and 1940; 4. Detectives, Traces, and Repetition in The Exploits of Elaine; 5. Repetition, Reiteration, and Reenactment: Operational Detection; 6. Sound Serials: Media Contingency in the 1930s; 7. Conclusion: Telefilm, Cross-Media Migration, and the Demise of the Film Serial; Index of Names; Index of Film Titles; Index of Subjects
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Film serials; ART -- Film & Video; PERFORMING ARTS -- Film -- History & Criticism; Theatre studies; Film theory & criticism; Electronic, holographic & video art; Film serials -- History; History; Electronic books; Electronic books; Electronic books